Commentary: Mobility, contexts, and the chronotope. (1st March 2017) - Blommaert, Jan
Abstract : Mobility raises specific issues with regard to what we understand by 'context', and in this commentary I suggest that Bakhtin's concept of chronotope could be a useful instrument enabling a precise and detailed, mobile, unit of 'context'. This unit connects specific time-space arrangements with ideological and moral orders, projecting possible and preferred identities. The articles in this issue offer rich material in this direction.